o que era simples imprensa virou mídia: Como o MST divulgou os meios de comunicacąõ de massa - Perli, Fernando [UNESP] (Universidade do Estado de Santa Catarina, 2017)
This article analyzes the construction of a political agenda of the Brazilian Landless Workers' Movement (MST) which dealt with the place occupied by the mass media in the demands of social movements in the 1980s and 1990s. The material studied comprises the Boletim Sem Terra, the Jornal Sem Terra e the Revista Sem Terra, all of which constituted a field of communication in defense of political projects in tune with the agrarian reform in Brazil.The production, distribution and use of the printed material to train cadres and publicize the MST organization were supported by civil society, intellectuals, journalists, trade unionists and landless leaders. From a variety of published themes, the present text delimits editorials, articles and opinion columns that expressed positions of MST national leadership before the coverages or the silencing by mainstream television, radio and newspapers concerning the mobilizations of landless rural workers.
what was simple press turned into media: How Brazilian MST spread mass media
Keywords: Brazilian Landless Workers; Mass Media; Movement; Press